Characterizing soils under various cash crops farming in the upland areas of Sarawak-A case study at Kruin area, Sabal - Ho, Soo Ying (Universiti Malaysia Sarawak (UNIMAS), 2012)
Population expansion and the need of cash income result in intensified upland agricultural practices globally. Even though efforts are progressing towards sustaining the agricultural practices in upland areas, however, limited studies discuss on the present condition of upland agricultural practice. This study discusses present soil fertility status and condition under various kinds of perennial cash crops farming (rubber, Hevea brasiliensis; pepper, Piper nigrum; oil palm, Elaeis guineensis; vegetables and fruits) in an upland area of Sarawak, Malaysia towards providing fundamental information and future perspective of the current farming practice. The study was conducted at Kruin village in Sabal, Serian. Soil samples were collected in each type of agricultural lands at the depths of 0-10cm and 30-40cm for soil physicochemical analysis. The results showed that the soils are sandy in texture with acidic nature which results in high Al saturation. The clay content is low with approximately 13.8 % at the study area. At different agricultural lands, soil exchangeable bases and total C were low and did not varied widely although some sites especially in the home garden showed significantly high level of exchangeable Ca. High level of exchangeable Ca in home garden probably due to the external input of soil with different parent material and ash effect from addition of burnt materials and left over unburned materials such as charcoal from household waste. At pepper farm, bulk density and soil hardness were high, indicating regular farming practices such as harvesting and weeding have resulted in considerable soil compaction. Based on the soil analysis, it can be concluded that current farming practice does not show much impacts to the soil, the chemicals levels in the soils were low, indicating little use of agrochemicals in the farming practice. However, technologies such as intercropping and crop rotation should be integrated into current farming practice to conserve soil fertility towards a more sustainable upland agriculture in the future.